Multi-stakeholder initiatives and decarbonization in the European food supply chain - Moreira-Dantas, Ianna Raissa; Martínez-Zarzoso, Inmaculada; de Araujo, Maria Luísa Fernandes; Evans, Judith; Foster, Alan; Wang, Xinfang; Thakur, Maitri; Jafarzadeh, Sepideh; Martin, Marta Pujol (Frontiers in Sustainability, 2023)
The European Green Deal is a political milestone aiming to promote a carbon-neutral economy in the European Union. Decarbonizing the complex food sector requires the unified interaction among effective climate policies, economic instruments, and initiatives involving multiple stakeholders. Despite increasing efforts to highlight the importance of innovations and finance to achieve sustainable food supply chains (FSC), comprehensive information about related opportunities and barriers to mitigating emissions in the food sector is still under-explored. To cover this gap, this paper applies an existing industrial policy framework under the lens of the EU FSC to identify potential strategies that should help achieve the needed financial means and innovation actions, as well as to gauge political alignment across FSC stages. Methodologically, the pillars proposed in the framework are linked to multi-stakeholders' initiatives engaged in achieving net-zero emissions. The paper highlights three main implications of the identified interlinkages. First, political directionality related to the food sector should be more comprehensively tailored to account for the specificities of all stages of the FSC. Second, research and development projects shall likewise cover all stages, instead of emphasizing only food production and agricultural systems. Finally, multiple stakeholders are crucial as promoters of technology and innovation towards a green economy. Nevertheless, initiatives should be integrated into political discussions in order to promote civil awareness, sustainable food and services demand, aligned to political guidelines.